Low molecular weight heparin in COVID-19: benefits and concerns - Makarem, Adham; Zareef, Rana; Abourjeili, Joseph; Nassar, Joseph E; Bitar, Fadi; Arabi, Mariam (Frontiers in Pharmacology, 2023)
Since its emergence, the COVID-19 pandemic had a dramatic impact on the public health worldwide and it scarred the medical, economical, and social determinants of health. Even after the significant vaccination advances, the disease of SARS-CoV-2 can manifest in severe presentations with life-threatening thromboembolic and multi-organ complications leading to notable morbidity and mortality. Clinicians and researchers are on continuous pursuit of investigating different approaches in the attempt to prevent the infection and minimize its severity. Although the COVID-19's pathophysiology remains relatively unclear, it is well established now that coagulopathy, systemic thrombotic propensity, and a robust immunoinflammatory response are some of the most important determinants of its morbidity and mortality. Accordingly, research efforts have focused on addressing the inflammatory and hematological cascades using available agents to avoid thromboembolic events. Several studies and investigators have emphasized the importance of Low molecular weight heparin (LMWH), namely Lovenox, in addressing these sequelae of the COVID-19 disease, either prophylactically or therapeutically. This review explores the benefits and concerns of employing LMWH, a widely used anticoagulant, in COVID-19 disease. It delves into Enoxaparin as a molecule, along with its pharmacology, mechanism of action, and clinical uses. It also reviews the current high-quality clinical evidence that highlight the role of enoxaparin in SARS-CoV-2 infection.